Doing news framing analysis : empirical and theoretical perspectives - D'Angelo, Paul; Kuypers, Jim A. (LEA's communication series., 2010)
"Suitable for those wishing to learn about news framing, this guide moves empirical inquiry forward, edifies analysts of framing and producers of frames, fosters understanding among the various scholarly camps of framing scholars, and urges greater clarity from framing analysts in various aspects their empirical inquiry"--Provided by publisher.